Effects of pre-analytical variables on flow cytometric diagnosis of canine lymphoma: A retrospective study (2009–2015). (February 2018) - Comazzi, S.; Cozzi, M.; Bernardi, S.; Zanella, D.R.; Aresu, L.; Stefanello, D.; Marconato, L.; Martini, V.
Highlights: Preanalytical variables affecting flow cytometric analysis of lymph node aspirates from dogs with lymphoma were evaluated Sample cellularity and presence of necrosis affected the likelihood of having diagnostic samples. Skilled sample collector and inclusion of blood and bone marrow influenced the possibility of having diagnostic results Flow cytometry yielded conclusive results in 90% of cases if sample quality and sampling conditions were adequate. Abstract: Flow cytometry (FC) is increasingly being used for immunophenotyping and staging of canine lymphoma. The aim of this retrospective study was to assess pre-analytical variables that might influence the diagnostic utility of FC of lymph node (LN) fine needle aspirate (FNA) specimens from dogs with lymphoproliferative diseases. The study included 987 cases with LN FNA specimens sent for immunophenotyping that were submitted to a diagnostic laboratory in Italy from 2009 to 2015. Cases were grouped into 'diagnostic' and 'non-diagnostic'. Pre-analytical factors analysed by univariate and multivariate analyses were animal-related factors (breed, age, sex, size), operator-related factors (year, season, shipping method, submitting veterinarian) and sample-related factors (type of sample material, cellular concentration, cytological smears, artefacts). The submitting veterinarian, sample material, sample cellularity and artefacts affected the likelihood of having a diagnostic sample. The availability of specimens from different sites and of cytological smears increased the odds of obtaining a diagnostic result. Major artefacts affecting diagnostic utility included poor cellularity and the presence of dead cells. Flow cytometry on LN FNA samples yielded conclusive results in more than 90% of cases with adequate sample quality and sampling conditions.